Progression of Financial Reporting in Czech Republic and its Regulation - Jana Ištvánfyová; Ladislav Mejzlík; Jiří Pelák (European Financial and Accounting Journal, 2010)
The development of a national accounting framework presents unique issues. A strong accounting system needs sufficient time to evolve. The influence of IFRS and of existing tax objectives of Czech accounting system increase the complexity and costs of implementing and monitoring the accounting rules. Given the short time between abandoning an economy based on public ownership and joining the European Union, Czech Republic made significant progress in development of its accounting regulation. The article addresses implementation of IFRS in the Czech Republic and describes the structure of accounting and auditing regulation which can be divided into four levels according to the reporting requirements set by the legislation. Major unsolved issues in the Czech national accounting system remain, including incomparability of Czech Accounting Standards and IFRS.
Keywords: M40; 650; International Financial Reporting Standards (IFRS); Development of Czech Accounting; Joining the European Union; Underdevelopment of accounting; Implementation of IFRS into Czech Accounting Regulation